A Reduction in Video Gaming Time Produced a Decrease in Brain Activity - Gong, Diankun; Yao, Yutong; Gan, Xianyang; Peng, Yurui; Ma, Weiyi; Yao, Dezhong (Frontiers in Human Neuroscience, 2019)
This study examines whether a decrease in brain development is observable after players have reduced their video gaming time over a period of 1 year. Both video gaming experts and non-experts were recruited, whose resting-state functional MRI (fMRI) data were collected at the beginning and the end of the study. Immediately after the first scan, the participants were instructed to spend no more than 3 h on video gaming weekly for 1 year. The results showed decreased self-reported video gaming skills and decreased amplitude of low-frequency fluctuation (ALFF) in the experts at the end of the study, demonstrating that a reduction in video gaming time over a period of 1 year produced a decrease in brain development. The non-experts served as a control group and had no significant changes. The findings support the adaptive effect of video gaming experience on brain and cognitive development.